Interactions of microalgae-bacteria consortia for nutrient removal from wastewater: A review. (June 2021) - Fallahi, Alireza; Rezvani, Fariba; Asgharnejad, Hashem; Khorshidi Nazloo, Ehsan; Hajinajaf, Nima; Higgins, Brendan
Abstract: Nitrogen and phosphorus pollution can cause eutrophication, resulting in ecosystem disruption. Wastewater treatment systems employing microalgae-bacteria consortia have the potential to enhance the nutrient removal efficiency from wastewater through mutual interaction and synergetic effects. The knowledge and control of the mechanisms involved in microalgae-bacteria interaction could improve the system's ability to transform and recover nutrients. In this review, a critical evaluation of recent literature was carried out to synthesize knowledge related to mechanisms of interaction between microalgae and bacteria consortia for nutrient removal from wastewater. It is now established that microalgae can produce oxygen through photosynthesis for bacteria and, in turn, bacteria supply the required metabolites and inorganic carbon source for algae growth. Here we highlight how the interaction between microalgae and bacteria is highly dependent on the nitrogen species in the wastewater. When the nitrogen source is ammonium, the generated oxygen by microalgae has a positive influence on nitrifying bacteria. When the nitrogen source is nitrate, the oxygen can have an inhibitory effect on denitrifying bacteria. However, some strains of microalgae have the capability to supply hydrogen gas for hydrogenotrophic denitrifiers as an energy source. Recent literature on biogranulation of microalgae and bacteria and its application for nutrient removal and biomass recovery is also discussed as a promising approach. Significant research challenges remain for the integration of microalgae-bacteria consortia into wastewater treatment processes including microbial community control and process stability over long time horizons. Graphical abstract: Image 1 Highlights: Wastewater nitrogen source governs interactions between microalgae and bacteria. Algae can induce oscillating oxygen levels that support P-accumulating bacteria. Bacteria can enhance the harvest efficiency of algae through secretion of EPS. Biogranulation of microalgae and bacteria creates highly-structure communities.